2008
DOI: 10.1159/000131081
|View full text |Cite
|
Sign up to set email alerts
|

Optical Methods for Measurements of Skin Penetration

Abstract: Fourier transform infrared photoacoustic (PAS), photothermal deflection (PDS) and Raman spectroscopy belong to the modern innovative noninvasive analytical tools that are beginning to be recognized as highly potential techniques for the noninvasive study of biological tissues and human skin under in vivo conditions. They can be applied to obtain information regarding the molecular composition of the skin down to several hundred micrometers below the skin surface. All three methods allow depth-resolved investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…[5] In skin research, numerous applications of infrared spectroscopy [6][7][8] and fluorescence microscopy [9][10][11] indicated the potential of noninvasive techniques for substance follow-up in human skin. Recently, confocal Raman microscopy (CRM) came in the center of interest in pharmaceutical research in general, [12,13] and skin research in particular.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In skin research, numerous applications of infrared spectroscopy [6][7][8] and fluorescence microscopy [9][10][11] indicated the potential of noninvasive techniques for substance follow-up in human skin. Recently, confocal Raman microscopy (CRM) came in the center of interest in pharmaceutical research in general, [12,13] and skin research in particular.…”
Section: Introductionmentioning
confidence: 99%
“…F inhomogeneity = A homogeneous /A inhomogeneous (1) A completely homogeneous distribution corresponds to a factor of inhomogeneity of 1. Higher F inhomogeneity values describe a more inhomogeneous distribution of the applied products on the skin.…”
Section: Definition Of a Factor Of Inhomogeneitymentioning
confidence: 99%
“…Optical spectroscopy can be a valuable tool to obtain qualitative and quantitative information on substances utilizing an appropriate absorption band [1][2][3] . A linear relationship exists between the spectroscopically measured absorbance and the concentrations of the absorbing species distributed homogeneously in the investigated system (Lambert-Beer law).…”
Section: Introductionmentioning
confidence: 99%
“…This problem was studied and described by many groups (36)(37)(38)(39)(40)(41)(42)(43)(44), and a recent study by Xiao et al, using multilayered systems constituted with polymers films with refractive indexes close to those of the human skin, showed that the error in the measurement led to an underestimation of the depth value of 15-20% (45). Therefore, all depth values deduced from Raman measurements should be theoretically corrected by applying a 15-20% factor.…”
Section: Confocal Raman Microscope Studiesmentioning
confidence: 99%